Clinical impact of low tube voltage computed tomography during hepatic arteriography with low iodine to detect hepatocellular carcinoma before transarterial chemoembolization. Issue 154 (September 2022) - Inoue, Akitoshi; Uemura, Ryo; Takaki, Kai; Sonoda, Akinaga; Ota, Shinichi; Nitta, Norihisa; Batsaikhan, Bolorkhand; Takahashi, Hiroaki; Watanabe, Yoshiyuki
Abstract: Purpose: This study aimed to evaluate the clinical impact of low tube voltage computed tomography (CT) during hepatic arteriography (CTHA) using low iodine contrast to detect hepatocellular carcinoma (HCC). Materials and methods: CTHA images were obtained using a dual-spin technique (80 kVp and 135 kVp) with 30 ml of low-dose iodine contrast (75 mgI/ml). Three radiologists reviewed 135 kVp and 80 kVp CTHA images to diagnose HCC, recording their confidence scores and evaluations of sharpness, noise, artifact, and overall image quality. Lesion-to-liver contrast ratios and objective noise were measured by a non-reader radiologist. Results: We included 23 patients (body mass index, 23.6 ± 2.6 kg/m 2 ) with 89 HCCs. The mean radiation dose index volume was 21.3 mGy at 135 kVp and 9.4 mGy at 80 kVp (P < 0.001). The overall sensitivity and positive predictive value for diagnosing HCCs at 80 kVp vs. 135 kVp were 0.787 vs. 0.730 and 0.712 vs. 0.756, respectively. The lesion-to-liver contrast ratio at 80 kVp was significantly higher than at 135 kVp in the first (3.1 vs. 2.0; P = 0.008) and second phase (3.1 vs. 2.3; P = 0.016). Objective noise was significantly higher at 80 kVp than at 135 kVp in the first (15. 6 ± 4.9 vs. 11.0 ± 3.1; P < 0.001) and second (16.9 ± 5.2 vs. 15.0 ± 7.3; P = 0.046) phases. Conclusion: An 80 kVp CTHA, with lower-dose iodine, improved the sensitivity and reduced the radiation dose, despite a decreased positive predictive value in comparison with a 135-kVp CTHA with the same iodine dose.